Assessment of diagnostic value of technetium-99m pyrophosphate myocardial scintigraphy in 80 patients with possible acute myocardial infarction. Issue 9 (September 1977) - Walsh, W F; Karunaratne, H B; Resnekov, L; Fill, H R; Harper, P V
Abstract : The diagnostic value of technetium-99m-pyrophosphate (Tc-pyrophosphate) myocardial scintigraphy was determined in 80 consecutive patients who had been admitted to the coronary care unit in order to rule out an acute myocardial infarction. Scintigraphic findings obtained within 5 days of admission were correlated with the final cardiac diagnosis determined for each patient. Significant myocardial uptake of Tc-pyrophosphate (positive scans) occurred in 13 of 22 patients (59%) who had enzyme and/or electrocardiographic proven acute myocardial infarct: 3 out of 5 with transmural myocardial infarct, 9 of 16 with nontransmural myocardial infarct, and 1 patient with left bundle-branch block. Of 58 patients who showed no evidence of acute myocardial infarction, positive scans occurred in 14 of 33 patients who had unstable angina pectoris (42%), 0 of 6 who had congestive heart failure, 6 of 9 who had other acute cardiac syndromes, and in 0 of 10 who had noncardiac chest pain. In the patients with unstable angina pectoris positive scans could not be predicted on the basis of the history, electrocardiographic findings or the arteriographically determined severity of the coronary artery disease. Blood levels of Tc-99m activity measured in 21 cardiac patients and in 6 volunteers did not correlate with the uptake intensity of Tc-pyrophosphate. These findings suggest caution in the use of this imaging method for the diagnosis of acute myocardial infarct in patients admitted with 'rule out myocardial infarction'.